2020
DOI: 10.1101/2020.08.19.20177980
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and correlation of symptoms and comorbidities in COVID-19 patients: A systematic review and meta-analysis

Abstract: Background: The COVID-19 affected millions of people, and the patients present a constellation of symptoms and comorbidities. We aimed to chronicle the prevalence and correlations of symptoms and comorbidities, and associated covariates among the patients. Methods: We performed a systematic review and meta-analysis [PROSPERO registration: CRD42020182677]. Databases [PubMed, SCOPUS, EMBASE, WHO, Semantic Scholar, and COVID-19 Primer] were searched for clinical studies published in English from January 1 to Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
3
5
1
Order By: Relevance
“…In the current study, based on gender distribution, covid-19 was detected in 16.69% females while amongst males it was detected in 19.16% patients (p=0.001).In accordance with our study, a high morbidity rate of covid-19 was observed in males as compared to females 16 .This might be due to involvement of males in outside home activities as compared to females due to which more males are exposed to the covid-19 infection. Another study also reported comparable results and shows that more males are infected by covid-19 as compared to females 21 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the current study, based on gender distribution, covid-19 was detected in 16.69% females while amongst males it was detected in 19.16% patients (p=0.001).In accordance with our study, a high morbidity rate of covid-19 was observed in males as compared to females 16 .This might be due to involvement of males in outside home activities as compared to females due to which more males are exposed to the covid-19 infection. Another study also reported comparable results and shows that more males are infected by covid-19 as compared to females 21 .…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, a total of 11444 patients were enrolled finally and based on polymerase chain reaction (PCR), covid-19 was detected in 18.25% patients.In accordance with our study, a recent study carried out by Fazal Rahman et al reported 22.4% morbidity rate in their study 16 .A recent study carried out by Sarah Arif et al reported 6% prevalence of covid-19 which is not in accordance with our study 17 .Other studies also reported contrasting results as compared to our findings 18,19 . A recent study reported 19% morbidity rate which is almost similar to our findings 20 .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The pandemic has rapidly swept across the globe infecting more than 122 million people, and more than 2.69 million people died as of 20 March, 2021 [2]. Since its rapid spread outside of Mainland China at the beginning of 2020, COVID-19 caused a serious global public health threat [3][4][5]. At its early phase in China, the number of cases were double at every 7.5 days, indicating a faster transmission of the virus [6].…”
Section: Introductionmentioning
confidence: 99%
“…Majority of the confirmed COVID-19 patients are asymptomatic but the potential to transmit the virus continues to be high. (11,12)…”
Section: Introductionmentioning
confidence: 99%